The Bitter End : The 2020 Presidential Campaign and the Challenge to American Democracy - Sides, John; Vavreck, Lynn, 1968-; Tausanovitch, Chris, 1985- (Book collections on Project MUSE., 2022)
"What are the priorities that drove voter behavior going into the 2020 election? What are the issues that most divide us, and how do these divisions manifest among different groups? How did Donald Trump speak to these issues in his presidency and reelection campaign? These are the kinds of questions that John Sides, Chris Tausanovitch, and Lynn Vavreck will explore in their new book. In the spirit of Sides and Vavreck's book The Gamble: Choice and Chance in the 2012 Election, and Sides, Tesler, and Vavreck's Identity Crisis: The 2016 Presidential Campaign and the Battle for the Meaning of America, the authors will emphasize the unique and historic features of the 2020 presidential race, as well as the important fundamentals that underlie all presidential elections, while presenting current political science research for a general audience. Drawing their data from a new initiative called The Nationscape Project, composed of 500,000 interviews conducted throughout the year and before the 2021 inauguration, the book promises to be a data-driven analysis of what really mattered in the 2020 campaign. The book's driving argument and ultimate message will be determined by the data, but their current plan is to devote chapters to the big ideas that are driving voters to the polls and determining support for various candidates, how these ideas align with party orientation, and how beliefs differ across various subgroups, determined by age, education, race, gender, and region. Laced throughout these findings will be narration of the unfolding election, supported by the authors' firsthand reporting, observations, and interviews with voters. Notably, the authors seek to explain the conditions that, despite the challenges and problems of the Trump presidency, nearly handed Trump a second term as President"--